Liver iron concentration measurements by MRI in chronically transfused children with sickle cell anemia: baseline results from the TWiTCH trial. Issue 9 (September 2015) - Wood, John C.; Pressel, Sara; Rogers, Zora R.; Odame, Isaac; Kwiatkowski, Janet L.; Lee, Margaret T.; Owen, William C.; Cohen, Alan R.; St. Pierre, Timothy; Heeney, Matthew M.; Schultz, William H.; Davis, Barry R.; et al.
<x xml:space="preserve">Abstract</x> Noninvasive, quantitative, and accurate assessment of liver iron concentration (LIC) by MRI is useful for patients receiving transfusions, but R2 and R2* MRI techniques have not been systematically compared in sickle cell anemia (SCA). We report baseline LIC results from the TWiTCH trial, which compares hydroxyurea with blood transfusion treatment for primary stroke prophylaxis assessed by transcranial Doppler sonography in pediatric SCA patients. Liver R2 was collected and processed using a FDA‐approved commercial process (FerriScan®), while liver R2* quality control and processing were performed by a Core Laboratory blinded to clinical site and patient data. Baseline LIC studies using both MRI techniques were available for 120 participants. LICR2* and LICR2 results were highly correlated (r2 = 0.93). A proportional bias of LIC(R2*)/LIC(R2), decreasing with average LIC, was observed. Systematic differences between LICR2* and LICR2 were also observed by MRI manufacturer. Importantly, LICR2* and LICR2 estimates had broad 95% limits of agreement with respect to each other. We recommend LICR2 and LICR2* not be used interchangeably in SCA patients to follow individual patient trends in iron burden.Am. J. Hematol. 90:806–810, 2015. © 2015 Wiley Periodicals, Inc.